2021
DOI: 10.4149/av_2021_207
|View full text |Cite
|
Sign up to set email alerts
|

DNA vaccine targeting the ectodomain of influenza M2 protein to endolysosome pathway enhances anti-M2e protective antibody response in mice

Abstract: A promising candidate for developing the universal influenza vaccine is the ectodomain of the M2 protein (M2e). We designed and prepared an experimental DNA vaccine with an improved potential to induce anti-M2e immune response. The sequence for truncated NS1 protein followed by 4xM2e was inserted into the expression vector pTriEx-4 (pEx). M2e repeats were fused to the transmembrane domain and cytoplasmic tail of lysosome-associated membrane glycoprotein 2 isoform A (LAMP-2a) to target the M2e to the endo-lysos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(60 reference statements)
0
0
0
Order By: Relevance
“…The article by Jaroslav Hollý et al described studies on M2e DNA vaccines and the results of the immunogenicity and protective properties of the vaccine were evaluated by administering the M2e DNA vaccine to BALB/c mice and performing viral challenge experiments, showing that the mice produced anti-M2e antibodies after vaccination with the M2e DNA vaccine. The survival rate of mice vaccinated with the M2e DNA vaccine was high after the viral challenge experiment [ 51 ]. Therefore, such studies indicated that the optimized M2e DNA vaccine could be a promising candidate for a universal influenza vaccine, inducing both humoral and cellular immune responses.…”
Section: Nucleic Acid Vaccinesmentioning
confidence: 99%
“…The article by Jaroslav Hollý et al described studies on M2e DNA vaccines and the results of the immunogenicity and protective properties of the vaccine were evaluated by administering the M2e DNA vaccine to BALB/c mice and performing viral challenge experiments, showing that the mice produced anti-M2e antibodies after vaccination with the M2e DNA vaccine. The survival rate of mice vaccinated with the M2e DNA vaccine was high after the viral challenge experiment [ 51 ]. Therefore, such studies indicated that the optimized M2e DNA vaccine could be a promising candidate for a universal influenza vaccine, inducing both humoral and cellular immune responses.…”
Section: Nucleic Acid Vaccinesmentioning
confidence: 99%